연안해역의 공간적 특성을 고려한 해양사고 특성 분석 - 양지민; Yang Ji Min; 노유나; Noh Yu Na; 권오훈; Kwon Oh Hoon (교통안전연구, 2021)
본 연구에서는 특정 기상 환경 조건일 때 발생하는 해양사고에 대한 특성에 대해 공간적으로 분석하고자 한다. 연안해역을 대상으로 해양 기상 환경 데이터와 해양사고 데이터를 공간 단위로 변환한 뒤 비슷한 기상 환경 조건을 가지는 공간 단위를 군집화하여 각 군집별 해양사고 발생에 관한 특성을 비교·분석하였다. 해양 사고 발생 특성 분석 결과, 군집1과 군집2에서 모두 단독 사고 유형이면서 기관손상 사고가 주로 가을과 08:00~12:00 사이에 가장 많이 발생하는 것으로 나타났으며, 이를 모비율 차이 검정을 통해 통계적으로 비교한 결과, 단독 사고유형, 기관손상 사고, 가을은 두 군집의 비율 차이가 있는 것으로 나타났지만 08:00~12:00 사이 시간대에서는 두 군집별 비율 차이가 없는 것으로 나타났다. In this study, we spatially analyze the characteristics of marine accidents occurring under certain meteorological conditions. After converting the meteorological environment data and marine accident data into spatial units, we clustered spatial units with similar meteorological environment conditions to compare and analyze the marine accident characteristics of each cluster. The spatial locations of Cluster2 are in the western sea area and southern sea area of the western region. According to the analysis of the characteristics of marine accidents, both Cluster1 and Cluster2, most frequently occurred accidents had a type of commercial damage of individual accidents in autumn between 08:00~12:00 am. A statistical comparison of the results of the two independent, population proportions tests, indicated that there was a difference in ratio between the type of individual accidents and commercial accidents in autumn but between 08:00~12:00 am showed no difference in proportions.